An Analysis of Bathroom and Toilet Interior Design According to the Capacity of the Elderly - Made Ida Mulyati; Levi Anatolia S.M.Exposto (Jurnal KESANS : Kesehatan dan Sains, 2022)
According to the World Health Organization (WHO), it is categorized as elderly if a person is 65 years old. At that age, the physical and psychological abilities of the elderly are decreasing. Since 2004, the President of Indonesia through Presidential Decree No. 2 of 2004, the government has aimed to improve social welfare by improving nursing home facilities, one of which is bathroom and toilet facilities. Given the accidents that most often occur to the elderly in the bathroom and toilet. This effort really needs to be done because the elderly's movement ability has decreased a lot due to a decrease in sensory and motor capacity. In addition, the nervous system of the elderly will experience changes marked by the death of cells in the brain continuously, this results in reduced blood supply to the brain. Such conditions cause a decrease in processing capacity will result in slow body reactions and decreased sensitivity of the five senses. Given this trend, there are more and more studies related to the bathroom for the elderly. The results of research from researchers that have been published in journals related to bathrooms and toilets for the elderly, no one has yet complexly analyzed the interior design of bathrooms and toilets for the elderly that are comfortable and safe. For this reason, before redesigning, it is necessary to analyze the interior design that is safe and comfortable according to the capacity of the elderly as users.